A scalable ball milling strategy to endow SnS anode electrodes with free volume property for enhanced electrochemical performance. (3rd May 2022) - Guan, Huibin; Feng, Dong; Liu, Qi; Zeng, Tianbiao
Abstract : SnS/G- x % anode with free volume has been fabricated by a scalable ball milling technology. The free volume effectively relief the volume expansion/shrinkage SnS, an optimized electrochemical performance is being made at graphite content of 15 wt%. Abstract : Among the tin-based composites, stannous sulfide (SnS) is a prospective material to serve as an anode for lithium-ion batteries (LiBs) owing to its high theoretical-capacity, layer-structure for fast Li + diffusion paths, and low toxicity. However, severe volume expansion/shrinkage exfoliates the electrode coating, leading to the severe loss of active materials. Herein, free volume was introduced into SnS to relieve the sequelae of volume expansion/shrinkage creatively, which effectively improved the cyclability of the SnS-based anode. The as-synthesized SnS/G-15% exhibited overall optimal electrochemical performances, i.e., the highest reversible capacity and best cyclability over pure SnS, SnS/G-5% and SnS/G-25%. Ex situ scanning electron microscopy images also illustrated that no cracks were generated in the cycled SnS/G-15% electrode. This work highlights an efficient and cost effective approach for the synthesis of long-cycle life and high-cyclability anodes.